EVALUASI KINERJA KEUANGAN PADA KOPWAN (BAITUT TAMWIL MUHAMMADIYAH) “DINAR SETIA” DESA MOJOKAMPUNG BOJONEGORO - Ika Puspita Sari (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2012)
This study aims to evaluate the performance of the cooperative would scope of financial ratio analysis to determine the financial performance. The scope of the health assessment and UJKS Cooperative KJKS includes assessment of several aspects as follows: capital, asset quality, management, efficiency, liquidity, independence and growth, cooperative identity, And Compliance Sharia. The population used in this thesis is a study of Financial Statements Kopwan BTM Dinar Mojokampung Bojonegoro Faithful Village from 2009 to 2011, consisting of a balance sheet and profit / loss. The data collection method used is the approach of Field Studies (Field Risearch). Pngumpulan engineering data through documentation, and questionnaires. Methods and techniques of data analysis using eight methods are: capital, asset quality aspects, management aspects, aspects of efficiency, liquidity aspects, aspects of independence and growth, and the cooperative aspects of identity keptuhan aspects of sharia. Total score achieved Kopwan BTM